Success Factors in Experiential Marketing - Case Studies from Italy - Tiuraniemi, Paula (My University, 2016)
This study is taking a look into the success factors in experiential marketing. Since the popularity of marketing actions that count into experiential has been increasingly used by world famous multinationals, such as Coca Cola and Red Bull, the interest towards the success factors of these kinds of marketing actions is growing. The intention is to find out how experiential marketing can give benefits for international brands. The goal is to define those variables that are impacting experiential marketing to meet the objectives that are set for the campaigns. Experiential marketing has gained increasingly growing attention since the millennium, and there are two major factors that need to be taken into account in the experiential success of international brands. Those factors are the expanding use of social media and the country specific consumer values in today’s international marketing environment. This thesis is exploring the topic by first studying previous literature and presenting earlier findings together with examples from some multinationals, and second, by building a deeper understanding of three case campaigns implemented in Italy. The data collection from the case studies is done mainly through interviewing field professionals, but also by viewing published materials from the cases. The cases were chosen within the criteria that they had been done for an international brand. Interviews were conducted in a qualitative way, and the type of the interview was semi-structured. The findings from the cases were analyzed and compared to each other. The results suggest that despite that all of the three experiential marketing cases had been done for a different type of a product, and targeting different kind of consumers, the found success factors, however, had a lot of similarities. Especially important factors were the interactive communication, suitable timing of the campaign and keeping the project continuous with storytelling.
Keywords: Experiential marketing; social media; culture; success factors; fi=Markkinointi|en=Marketing|; fi=Master's Degree Programme in International Business|